Cello: desenvolvimento e aplicabilidade do jogo para o ensino da bioquímica - Bittencourt, Larissa Soares (2022)
Teaching Biochemistry has always been a challenge in the final stages of high school. The difficulty in learning may be associated with the difficulty of abstraction required in addition to the assimilation of interdisciplinary contents of biology and chemistry that mainly explain the metabolic pathways. With regard to abstraction, it was possible to identify, from the analysis of articles, an advance in the use and application of technological tools aimed at the teaching of Biochemistry, which seek to assist in the visualization of metabolic pathways and the application of various languages that aim to assist in the understanding of the content. Regarding the issue related to the metabolic pathway that uses carbohydrates in the production of ATP, called cellular respiration, it was noticed that the existing technological tools (applications and games, for example) did not contemplate some topics such as a glossary and self-assessment, necessary to assist in the teaching-learning process. This research aimed to act on a better understanding of cellular respiration through the development of an educational digital game entitled “Cello”, aimed at learning the first metabolic pathway of carbohydrates, called glycolysis. The digital game was developed in ten phases, corresponding to the stages of glycolysis. The technological tool is presented in the form of a Role Playing Game (RPG) and has a central character (Kondri) and some No Playable Characters (NPCs) such as Golgi, Lise and Ribo, representing the Golgi Complex, the lysosome and the ribosome. In order to understand in which moment of the teaching process the digital game would have the possibility of being inserted, the proposal of the three pedagogical moments was analyzed. It was identified that Cello digital game can be applied during the second moment, characterized by the organization of knowledge. Also as a result of this research, it was possible to observe some of the existing gaps in the teaching of biochemistry, such as the lack of interdisciplinarity between biology and chemistry and the need to strengthen teacher training for the teaching of Biochemistry.